Search for exotic S=-2 baryons in pp̄ collisions at s=1.96TeV - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
A search for a manifestly exotic S=-2 baryon state decaying to Ξ-π-, and its neutral partner decaying to Ξ-π+, has been performed using 220pb-1 of pp̄ collisions at s=1.96TeV collected by the Collider Detector at Fermilab. The Ξ- trajectories were measured in a silicon tracker before their decay, resulting in a sample with low background and excellent position resolution. No evidence was found for S=-2 pentaquark candidates in the invariant mass range of 1600-2100MeV/c2. Upper limits on the product of pentaquark production cross section times its branching fraction to Ξ-π+,-, relative to the cross section of the well-established Ξ(1530) resonance, are presented for neutral and doubly negative candidates with pT>2GeV/c and |y|<1 as a function of pentaquark mass. At 1862MeV/c2, these upper limits for neutral and doubly negative final states were found to be 3.2% and 1.7% at the 90% confidence level, respectively. © 2007 The American Physical Society.